Proton Holdings : A Case Study - Abdullah, Elena Chiang (2005)
The study was an overall analysis of the company, its performance, the challenges and the effectiveness of the actions that has been taken. The study also proposes strategies and an action plan based on a detailed strategic analysis of Proton to enable the company to remain competitive.